2016
DOI: 10.3732/ajb.1600097
|View full text |Cite
|
Sign up to set email alerts
|

Direct vs. indirect effects of whole‐genome duplication on prezygotic isolation inChamerion angustifolium: Implications for rapid speciation

Abstract: Genome duplication causes phenotypic shifts and contributes directly to prezygotic isolation for some barriers (gametic isolation) but cannot account for the cumulative isolation from diploids observed in natural tetraploids. Therefore, conditions for species formation through genome duplication are not necessarily instantaneous and selection to strengthen prezygotic barriers in young polyploids is critical for the establishment of polyploid species in sympatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 64 publications
5
84
2
1
Order By: Relevance
“…This lends tentative support to suggestions that WGDs may fuel species diversification (27), possibly via the establishment of reproductive barriers (31).…”
Section: Massive Wgds In Malpighiales-our Analyses Identify An Impressupporting
confidence: 71%
See 1 more Smart Citation
“…This lends tentative support to suggestions that WGDs may fuel species diversification (27), possibly via the establishment of reproductive barriers (31).…”
Section: Massive Wgds In Malpighiales-our Analyses Identify An Impressupporting
confidence: 71%
“…In these cases, the potential adaptive value of WGDs is thought to arise from the origin of genetic novelties (19)(20)(21)(22) and by masking the effects of deleterious mutations (23), which may facilitate plant survival across periods of global disruption. Although debate exists as to the influence of WGD on speciation and enhanced species diversification rates (14,(24)(25)(26)(27)(28), it is generally accepted that chromosomal rearrangements from WGDs can significantly accelerate isolating barriers, thus promoting cladogenesis (29)(30)(31). In short, it is established that WGDs are a prominent feature of vascular plant evolution, but the respective phylogenetic distribution, timing, and significance of these ancient events remains unclear.Here, we investigate WGDs in the large and diverse angiosperm order Malpighiales, which contains more than 16,000, mostly tropical, species with tremendous morphological and ecological diversity.…”
mentioning
confidence: 99%
“…from the same taxonomic complex) within and beyond the total geographic range are a powerful approach for assessing whether polyploids confer fitness advantages in extreme environments lacking diploids (e.g., Ramsey, 2011;McIntyre & Strauss, 2017). Additional studies are needed to determine whether observed differences between cytotypes of different ploidy levels arise immediately as a result of polyploidization or have evolved over time since the genome duplication event (Ramsey, 2011;Husband et al, 2016). between range size and each predictor variable, which was then transformed to Fisher's z, a metric of standardized effect size for correlations (Koricheva et al, 2013; Methods S1). The final dataset included 123 estimates of z across five categories of intrinsic predictors (dispersal ability, mating system, ploidy, niche breadth, species' age), three categories of extrinsic predictors (range position, environmental heterogeneity, and niche availability), and three categories of range size metrics as responses (area, extent, or filling; Methods S1).…”
Section: Box 3 Ploidy and Range Sizementioning
confidence: 99%
“…Another nonexclusive explanation for this segregation pattern relies on a differentiation in the biotic niche (Wisz et al, 2013). Divergence in pollinator spectra and/or visit frequency have been found in other polyploids (Kennedy et al, 2006;Thompson & Merg, 2008;Husband et al, 2016). In D. broteri, the reproductive biology of 29, 49 and 69 cytotypes is unknown, but the dodecaploids have showed an extremely specialized pollination (Balao et al, 2011b).…”
Section: Autopolyploidy Niche Evolution and Competitive Interactionsmentioning
confidence: 99%